Unifying Dual-Pyramid Structure and Y–G Channel Synergy for Full-Reference Image Quality Assessment - Ali Abdulazeez Mohammed Baqer Qazzaz; Yousif Samer Mudhafar; Siraj Muneer Mahboba (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Standard metrics such as SSIM often overlook complex chromatic distortions, creating a gap between objective scores and human judgment. To address this, we present the Synergistic Structural Similarity Index (SSSI), a metric grounded in a novel dual-pyramid strategy that integrates Gaussian-blurred stability with direct subsampling sharpness. Our method departs from luminance-only analysis by employing an equal, synergistic partnership between the luminance (Y) and Green (G) channels, mirroring the eye's spectral sensitivity. On the KADID-10k dataset, SSSI achieves an SROCC of 0.7793. This represents a significant 4% performance gain over the standard SSIM baseline, demonstrating that integrating chromatic data with dual-scale structural analysis provides a more accurate proxy for human visual perception.